PENGARUH PERSON-ORGANIZATION FIT TERHADAP MOTIVASI KERJA DAN KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KOMITMEN ORGANISASIONAL DAN DAMPAKNYA TERHADAP KINERJA (STUDI PADA PEGAWAI KANTOR SKADRON-31/SERBU PUSAT PENERBANGAN TNI AD (Jurnal Mahasiswa Pasca Sarjana, 2014)
Performance shown is the actual behavior of each person as an accomplishment of work produced by the employee in accordance with its role within the organization. Performance of something that is very important in order to achieve organizational goals. Therefore, high performance should be owned by every employee that she worked for the organization is able to competition and have hope in the future. The purpose of this study is to examine and analyze whether there is "The Effect of person-organization fit on Job Motivation And Job Satisfaction And Its Impact on Organizational Commitment and Its Impact on Employee Performance". (Study On Employee Skadron-31/Serbu of Army Aviation Center Office). This study is the Employee object Skadron-31/Serbu of Army Aviation Center Office as much as 158 people. This study uses the method of proportional random sampling of 114 respondents, the number of samples distributed to each group so that the samples taken rank representative population characteristics. As for how decision- done lottery so that each sample has the same chance or opportunity for any element or selected members of the population to be sampled . The analysis technique used in this study is the Statistical Package for the Social Sciences (SPSS) version 16.0. The results show the person-organization fit has a positive effects on job motivation, person-organization fit has a positive effects on job satisfaction, person-organization fit has not a positive effects on organizational commitment, job motivation has a positive effects on job satisfaction. Motivation is has not a positive effects on organizational commitment, job satisfaction has a positive effects on organizational commitment, job motivation has a positive effects on employee performance, job satisfaction has a positive effects on employee performance, organizational commitment has a positive effects on the performance employees, person-organization fit has not a positive effects on employee performance and job motivation, job satisfaction and organizational commitment is an effective mediating variable between person-organization fit with the employee performance of the Skadron-31/Serbu Puspenerbad. Keywords: Person-organization fit (P-O fit), job motivation, job satisfaction, organizational commitment and employee performance